COST EFFECTIVENESS OF LOCALLY MANUFACTURED ORTHOPAEDIC IMPLANTS: Locally Manufactured Orthopaedic Implants - Khan, Lt Col Zubair Ahmed; Arif, Muhammad; Saqib, Rizwan (Pakistan Armed Forces Medical Journal, 2012)
Objectives: To study clinical outcome and cost effectiveness in patients treated with locally manufactured orthopaedic implants. Type of study: Quasi experimental study Time and Place of study: The study was conducted in department of Orthopaedic Surgery CMH Nowshera from Sep 2009 to Aug 2011. Patients and Methods: All patients irrespective of age and gender, who were operated and applied orthopaedic implants, were included in the study. Good quality, cost effective locally manufactured orthopaedic implants were used in all cases. Clinical outcome was observed periodically and side effects like implant breakage, implant loosening and significant infection were recorded. Follow up period ranged from 6 months to 1 year. Descriptive statistics were used for data analysis. Results: Total 123 patients completed the study and all had satisfactory clinical outcome and no case of implant breakage, implant loosening and significant infection was seen. Conclusion: Locally manufactured implants can effectively be used without any significant side effects in place of costly branded counterparts.